Factors that Influence Generation Z Muslim Buying Behavior Towards Halal Culinary Product - Febrianti, Putri; Trapsila, Aji Purba (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The halal industry has become one of the fastest-growing business sectors in the global market. Indonesia, as the country with the second-largest Muslim population in the world, has significant potential for the development of the halal industry, particularly in the food and beverage sector. Although the government has enacted Law Number 33 of 2014 concerning Halal Product Assurance, the increasing interest in halal food products has not been accompanied by an equitable distribution of halal certification, especially among micro, small, and medium enterprises (MSMEs). This condition highlights the importance of examining the factors that influence purchase intention and purchasing behavior of halal culinary products, particularly among Generation Z. This study aims to analyze the factors influencing purchase intention of halal culinary products using the Theory of Planned Behavior (TPB) and to examine the effect of purchase intention on purchasing decisions. A quantitative approach was employed using primary data collected through questionnaires distributed to Muslim Generation Z consumers in Malang City. The data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results indicate that halal certification, attitude, subjective norms, and perceived behavioral control have a significant effect on purchase intention, while religiosity and halal awareness do not have a significant effect. Furthermore, purchase intention was found to significantly influence halal culinary product purchasing decisions.